Chronic Pain among Children with Cerebral Palsy Attending a Ugandan Hospital: A Cross-Sectional Study - Bambi, Emma Nsalazi; Mwesige, Angelina Kakooza; Lekuya, Hervé Monka; Kasirye, Philip; Idro, Richard (Researchsquare, 2021)
Children with cerebral palsy (CP) frequently experience chronic pain. The burden and severity of such pain is often underestimated in relation to their other impairments.Recognition and awareness of this chronic pain among children with CP constitute the cornerstone for caretakers and clinicians to improve the quality of life of those children. This study aimed to determine the prevalence of chronic pain among children with CP, and the factors associated. A cross-sectional study of children with CP, aged 2 – 12 years, attending the CP rehabilitation clinic and Pediatric Neurology Clinic at Mulago Hospital, Uganda from November 2017 to May 2018. A detailed history and clinical examination were performed and the co-morbidities were determined. CP was classified using the Gross Motor Function Classification System (GMFCS), Manual Ability Classification System, Communication Function Classification System (CFCS), and the Eating and Drinking Ability Classification System (EDACS) and documented with the level of impairment in the different domains. Pain was assessed by using the revised Face, Legs, Activity, Consolability, Cry pain scale.A total of 224 children with CP were enrolled. The prevalence of chronic pain was 64.3%. The majority had spastic bilateral CP (77.8%), moderate pain lasting over 6 months, and none of them was on long-term pain management. Epilepsy (60.9%), behavioral problem (63.2%), hearing impairment (66,7%), learning problem (67,6%), dental caries (75%), gastro-esophageal reflux (75%), sleep disorders (79.5%), vision impairment (80%), and malnutrition (90%) were comorbid conditions of chronic pain in children with CP in this study. The factors independently associated with chronic pain among children with CP were the GMFC system level 4 & 5, CFCS level 4 & 5, EDACS level 4 & 5, female children, and caretaker aged more than 30 years.Two-thirds of children with CP attending rehabilitation in this hospital had chronic pain. None was receiving pain management. Chronic pain was associated with the presence of multiple co-morbidities and more severe disability. Rehabilitation and care programs for children with CP should include assessment of pain in routine care and provide interventions for pain relief in children with CP even at an early age.
Keywords: Chronic pain, cerebral palsy, comorbid conditions, motor function, associated factors